Visually engaged ethnography: constructing knowledge and critical consciousness. Issue 2 (1st September 2016) - Bell, Travis R.
ABSTRACT: Engaged ethnography requires a deep rationale for involvement and a passion for a particular cause. Visual ethnography implements an aesthetic component, compliment, or fold into that complex, multi-layered engagement. This theoretical research attempts to move beyond traditional, epistemic debates and blend anthropological, communicative, and sociological concepts to form a cohesive approach to knowledge construction that exposes power, educates on publicly important issues, and reaches a critical consciousness to visually engage the public sphere. It is through that effort to recognize when a break from the shackle of our own limits of consciousness can create previously unattainable knowledge.